The Role of Love in Ethical Development Beyond Family and Friendship in Confucianism: Insights from Matteo Ricci’s On Friendship - Mark Kevin S. Cabural (Religions)
The family is a form of human relationship or organization that has been vital to the Chinese, influencing various aspects of its tradition. At its core lies the parent-child relationship, which emphasizes the virtue of filial piety (xiao 孝) and serves as the beginning of ethical development. Beyond the family, friendship is another form of human relationship that can also contribute to ethical development but is seen only as an extension of the development that begins in the family. This article aims to discuss how friendship, as articulated in Matteo Ricci’s On Friendship (Li Madou 利玛窦, 1552–1610; Jiaoyou Lun 交友论), can deepen or contribute to ethical development that begins in the family and extends into friendship, as understood in the Confucian tradition. The discussion places particular emphasis on the role of love as it emerges in Ricci’s text. The overarching argument of this article is that Ricci’s understanding of love, which is the indispensable element that binds friends together, can contribute to strengthening the ethical development that originates from the family and extends into friendship, as understood in Confucianism.